Pteridophytes (Lycophyta and Monilophyta) from Mosqueiro Island, municipality of Belém, Pará State, Brazil - Costa, Jeferson Miranda; Pietrobom, Marcio Roberto (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2007)
This works presents a floristic survey of the pteridophytes (Lycophyta and Monilophyta) from Mosqueiro Island, municipality of Belém, Pará State. This island comprises an area of 22,000 ha with high richness of habitats, including large natural forest remnants, favoring an elevated diversity of pteridophytes species. In the study area, 18 families, 34 genera and 70 species (five Lycophyta and 65 Monilophyta) were recorded. The families with the largest number of species were Hymenophyllaceae and Pteridaceae with 12 species each, followed by Dryopteridaceae with ten species and Polypodiaceae with seven species. The most representative genera were Trichomanes L., with ten species, Elaphoglossum Schott. ex J. Sm. with six species and Adiantum L. with four species. Seven species are new references for the Pará State (Salpichlaena hookeriana (Kuntze) Alston, Elaphoglossum obovatum Mickel, E. styriacum Mickel, Trichomanes trollii Bergdolt, Triplophyllum angustifolium Holttum, Hecistopteris kaieteurensis Kelloff & G.S. McKee and Thelypteris macrophylla (Kunze) C.V. Morton). The latter species is a new record to the northern region of Brazil as well.
Keywords: Floristic; Ferns and allied plants; Mosqueiro Island